Roles of helminth extracellular vesicle-derived let-7 in host–parasite crosstalk - Zhong, Haoran; Guan, Guiquan; Jin, Yamei (Frontiers in Immunology, 2024)
Helminth infections are a major public health problem as they can cause long-term chronic infections in their hosts for which there is no effective vaccine. During the long-term interaction between helminths and their hosts, helminth-derived extracellular vesicles (EVs) can participate in host immunomodulatory processes by secreting bioactive molecules (BMAs). Growing data suggests that microRNAs (miRNAs) in helminth EVs have a significant impact on the host's immune system.The let-7 family is highly conserved among helminth EVs and highly homologous in the host, and its function in host-parasite crosstalk may reflect active selection for compatibility with the host miRNA machinery. In-depth studies targeting this aspect may better elucidate the mechanism of parasite-host interactions. Hence, this review summarizes the current studies on the cross-species involvement of helminth EVderived let-7 in host immune regulation and discusses the barriers to related research and potential applications of helminth EVs.